Pengujian Kebocoran Apron Tahun 2019 - Oktavia Puspita Sari; Dila Nelvo Dasril; Chairun Nisa; Almaiza Almaiza (Jurnal Imejing Diagnostik (JImeD), 2020)
Background: Based on observations made by researchers found incorrect apron storage. According to Permenkes No. 1250 of 2009, storage and placement of Pb aprons may not be folded and may not be hung. The purpose of this study is to determine whether or not there are leaks in the apron.Method: Types of quantitative research approaches with experimental approaches. This research was conducted at the radiology installation. The testing is done by giving x-ray exposures on the surface of the apron. Based on the results of the exposure, the extent of the leak is in the apron. The measurement results will be compared with the theory Lambert 2001.Results: According to Lambert, apron leakage is still acceptable if the critical area is less than 15 mm2 and if the non-critical area is less than 670 mm2. The results showed that of the 15 aprons studied three aprons leaked, namely apron 4, apron 7, and apron 13 with each leakage area being 562.84 mm2, 312,174 mm2, 14,304 mm2 71,818 mm2.Conclusion: The total number of tested was 15 aprons, 3 aprons leaked and there was 1 apron which had no leakage. Leakage is caused by often placing an apron on the back of a chair, hanging an apron on a hanger, dropping an apron on the floor, and folding an apron on an examination table. Apron storage should be placed on a special rack in a horizontal position so as not to cause indentations or fractures on the lead.